Implementation Cycles - Shleifer, Andrei (Journal of Political Economy, 1986)
The paper describes an artificial economy in which firms in different sectors make inventions at different times but innovate simultaneously to take advantage of high aggregate demand. In turn, high demand results from simultaneous innovation in many sectors. The economy exhibits multiple cyclical equilibria, with entrepreneurs' expectations determining which equilibrium obtains. These equilibria are Pareto ranked, and the most profitable equilibrium need not be the most efficient. While an informed stabilization policy can sometimes raise welfare, if large booms are necessary to cover fixed costs of innovation, stabilization policy can stop all technological progress.